Human renal response to furosemide: Simultaneous oxygenation and perfusion measurements in cortex and medulla. (21st May 2019) - Haddock, Bryan; Larsson, Henrik B. W.; Francis, Susan; Andersen, Ulrik B.
Abstract: Aim: Disturbances of renal medullary perfusion and metabolism have been implicated in the pathogenesis of kidney disease and hypertension. Furosemide, a loop diuretic, is widely used to prevent renal medullary hypoxia in acute kidney disease by uncoupling sodium metabolism, but its effects on medullary perfusion in humans are unknown. We performed quantitative imaging of both renal perfusion and oxygenation using Magnetic Resonance Imaging (MRI) before and during furosemide. Based on the literature, we hypothesized that furosemide would increase medullary oxygenation, decrease medullary perfusion, but cause minor changes (<10%) in renal artery flow (RAF). Methods: Interleaved measurements of RAF, oxygenation ( T 2 *) and perfusion by arterial spin labelling in the renal cortex and medulla of 9 healthy subjects were acquired before and after an injection of 20 mg furosemide. They were preceded by measurements made during isometric exercise (5 minutes handgrip bouts), which are known to induce changes in renal hemodynamics, that served as a control for the sensitivity of the hemodynamic MRI measurements. Experiments were repeated on a second day to establish that the measurements and the induced changes were reproducible. Results: After furosemide, T 2 * values in the medulla increased by 53% ( P < 0.01) while RAF and perfusion remained constant. After hand‐grip exercise, T 2 * values in renal medulla increased by 22% ± 9% despite a drop in medullary perfusion of 7.2% ± 4.7% and a decrease in renal arterial flow of 17.5% ± 1.7% ( P < 0.05). Mean coefficients of variation between repeated measurements for all parameters were 7%. Conclusion: Furosemide induced the anticipated increase in renal medullary oxygenation, attributable exclusively to a decrease in renal oxygen consumption, since no change of RAF, cortical or medullary perfusion could be demonstrated. All measures and the induced changes were reproducible.